British Tank Production and the War Economy, 1934-1945. - Coombs, Benjamin (Bloomsbury Publishing, 2013)
British Tank Production and the War Economy, 1934-1945 explores the under-researched experiences of the British tank industry in the context of the pressures of war. Benjamin Coombs explores the various demands placed on British industry during the Second World War, looking at the political, military and strategy pressures involved. By comparing the British tank programme with the Canadian, American, Russian and Australian equivalents, this study offers an international perspective on this aspect of the war economy. Topics covered include the premature contraction of the tank programme and dep.